2011
DOI: 10.1186/1475-2875-10-206
|View full text |Cite
|
Sign up to set email alerts
|

Wide cross-reactivity between Anopheles gambiae and Anopheles funestus SG6 salivary proteins supports exploitation of gSG6 as a marker of human exposure to major malaria vectors in tropical Africa

Abstract: BackgroundThe Anopheles gambiae gSG6 is an anopheline-specific salivary protein which helps female mosquitoes to efficiently feed on blood. Besides its role in haematophagy, gSG6 is immunogenic and elicits in exposed individuals an IgG response, which may be used as indicator of exposure to the main African malaria vector A. gambiae. However, malaria transmission in tropical Africa is sustained by three main vectors (A. gambiae, Anopheles arabiensis and Anopheles funestus) and a general marker, reflecting expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 25 publications
6
56
1
Order By: Relevance
“…The same immunogenic proteins in different Anopheles mosquitoes, such as SG6, may trigger wide cross-reactivity between Anopheles species (31) . This universal characteristic of immunogenic proteins may improve their applicability as malaria vaccines in different regions.…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
“…The same immunogenic proteins in different Anopheles mosquitoes, such as SG6, may trigger wide cross-reactivity between Anopheles species (31) . This universal characteristic of immunogenic proteins may improve their applicability as malaria vaccines in different regions.…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
“…The sera used for our human IgG response study had previously identified two Anopheles salivary protein candidates that are highly antigenic and potential biomarkers for exposure to mosquito bites (Ali et al, 2012). Several other studies have also identified such salivary protein candidates as biomarkers for exposure to mosquito bites and estimates of malaria transmission (Proietti et al, 2013; Rizzo et al, 2011, 2014; Stone et al, 2012; Ya-Umphan et al, 2017). The low IgG response to AgTRIO suggests a natural lack of antigenicity following mosquito exposure.…”
Section: Discussionmentioning
confidence: 99%
“…funestus ). This cross-recognition could result from shared epitopes among these orthologous SG6 proteins [38,86]. According to their low molecular weights (approximately 11.7 and 13 kDa, respectively), gSG2 and gSG6 proteins should be contained in the large 11 kDa antigenic band detected in the Cellia subgenus.…”
Section: Discussionmentioning
confidence: 99%
“…These antibody responses were described as being short lived and linked to the level of exposure [28,30,31], highlighting the potential use of these responses to arthropod saliva antigens as immunological markers to evaluate individual exposure to arthropod bites [32] or assess the impact of vector control interventions [33]. Several studies demonstrated the presence of cross-reactive antibody responses against salivary proteins from different hematophagous arthropod species [34-38]. This cross-reactivity was attributed to the existence of antigens shared among different vector species [39].…”
Section: Introductionmentioning
confidence: 99%